KFSR's Dog Dish features ASI's sex offender resolution Sept. 14 - Uribes, Tom::::::::: (2013)
A resolution under consideration by the Associated Students Inc. (ASI) Student Senate about registered sex offenders will be the topic of this week's ASI Dog Dish radio show.